Identification and metabolic characteristics of an apolipoprotein C-II variant isolated from a hypertriglyceridemic subject - Huff, MW; Evans, AJ; Wolfe, BM; Connelly, PW; Maguire, GF; Strong, WL (Journal of lipid research, 1990)
The very low density lipoprotein (VLDL) apolipoproteins from a Type IV hypertriglyceridemic Caucasian subject (plasma TG: 645 mg/dl) and his brother (plasma TG: 328 mg/dl) were separated by isoelectric focusing gel electrophoresis (IEF) and found to contain two isoforms of apoC-II, identified by immunoblot. These corresponded to normal apoC-II-1 (isoelectric point: pI 4.88) and a variant isoform (apoC-II-v, pI 4.74). The pI of C-II-v was not altered by neuraminidase treatment, indicating that it was not sialylated. The concentration of total immunoreactive C-II in VLDL was elevated (18 mg/dl vs normal; 5.0 +/- 2 mg/dl) but similar to that in other Type IV subjects. In VLDL, which contained 90% of the plasma immunoreactive apoC-II, the ratio (by IEF) of C-II-1:C-II-v was 2:1, whereas in high density lipoproteins (HDL) the ratio was 1:1. VLDL apoB turnover was measured after the pulse injection of 125I-labeled VLDL. VLDL apoB kinetic parameters for the proband and four Type IV subjects were similar: production rate, 28 mg/kg per day versus 30 mg/kg per day; fractional catabolic rate, 1.62.day-1 versus 1.96.day-1; and pool size, 17 mg/kg versus 18 mg/kg. The decline in VLDL triglyceride (TG) after the infusion of heparin (9,000 IU over 4 h) was also similar to that observed in Type IV subjects. In VLDL, the fractional catabolic rates of apoC-II-1 and C-II-v were similar (C-II-1: 0.31.day-1, C-II-v: 0.29.day-1) whereas in HDL, although similar to each other, the rates were greater than in VLDL (C-II-1: 0.48.day-1, C-II-v: 0.44.day-1). VLDL and HDL from the proband were normal in their ability to activate bovine skim milk lipase, compared to Type IV VLDL and HDL without C-II-v. Purified apoC-II-1 and apoC-II-v activated the milk lipase to a similar extent (at 1 microgram of C-II; C-II-1: 34 units/h, C-II-v: 35 units/h). Thus, apoC-II-v is a newly recognized isoform of apoC-II-1. It remains to be determined whether this mutation plays a role in the genesis of hypertriglyceridemia.